Theatres of India : A Concise Companion - Edited by Lal, Ananda (New Delhi Oxford University Press, 2009)
Theatres of India is a comprehensive and accessible guide to theatre in India. The volume includes twenty-three detailed entries on the regional theatres of India, as well as a selection of India-specific theatre entries that span both rural and urban modes of Indian performance traditions over 2000 years.
Include Illustrations and Bibliography
Keywords: Theater -- India